A high–performance SPIHT–based image and video codec for surveillance. (22nd April 2013) - Mohanty, Bibhuprasad; Verma, Pramod Kumar; Mahapatra, Sudipta
A novel extension to wavelet transformed image and video codec based on SPIHT is presented for the purpose of surveillance where the detail information regarding a scene is not an essential requirement. A pre–processing scheme, called Zero–Shifting, has been proposed using which calculation of transformed coefficients becomes more consistent. This modification leads to a significantly higher PSNR and better visual quality at a specific bit rate with little additional computational complexity. We achieved 1.5–4.2 dB more gain at the lowest possible bit rate without using entropy coder, which provides only 0.3–0.6 dB increase in gain at the cost of higher computational complexity and reduced speed of the SPIHT codec.